2013
DOI: 10.1123/tsp.27.3.296
|View full text |Cite
|
Sign up to set email alerts
|

The Existence of Sport Psychology Services Among NCAA Division I FBS University Athletic Departments and Counseling Centers

Abstract: One hundred twenty university counseling centers and athletic-department websites were viewed and analyzed for the provision of sport psychology services specifically to NCAA (National Collegiate Athletic Association) Division I Football Bowl Championship Series (FBS) student athletes. Using content-analysis methodology, the present research identified a fair number of university athletic departments (n = 29) and university counseling centers (n = 6) that provided specific sport psychology services. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 14 publications
0
23
1
Order By: Relevance
“…In a review of NCAA Division I athletic department and counseling centers' websites, it was found that less than a third of the universities were providing sport psychology services to their athletes (Hayden, Kornspan, Bruback, Parent, & Rodgers, 2013). These numbers are similar to a 2001 study conducted by Voight and Callaghan, which may suggest that the market has not grown significantly among NCAA institutions.…”
Section: Discussionmentioning
confidence: 86%
“…In a review of NCAA Division I athletic department and counseling centers' websites, it was found that less than a third of the universities were providing sport psychology services to their athletes (Hayden, Kornspan, Bruback, Parent, & Rodgers, 2013). These numbers are similar to a 2001 study conducted by Voight and Callaghan, which may suggest that the market has not grown significantly among NCAA institutions.…”
Section: Discussionmentioning
confidence: 86%
“…Though there appears to be more sport psychology services available in intercollegiate athletics today than in previous years (c.f., Donohue et al, 2004;Hayden et al, 2013;Voight & Callaghan, 2001;Weinberg & Gould, 2011;Wilson et al, 2009), widespread integration and the significant levels of employment of SPPs predicted by earlier investigators remain to be achieved (Carr, 2007;Kornspan & Duve, 2006;Silva, Conroy, & Zizzi, 1999). While much of the previous research has provided valuable information regarding the status of sport psychology services at NCAA institutions, no studies to date have examined the specific characteristics of sport psychology positions that AAs find most attractive (e.g., what are they looking for?).…”
mentioning
confidence: 91%
“…Similar to Voight and Callaghan (2001), subsequent studies have obtained findings that sport psychology services are provided by a wide-array of individuals with various position formats (Hayden, Kornspan, Bruback, Parent, & Rodgers, 2013;Kornspan & Duve, 2006;Wilson, Gilbert, Gilbert, & Sailor, 2009). Investigations have revealed access to sport psychology services at one third (Hayden et al, 2013), one half (Voight & Callaghan, 2001), and three quarters of NCAA DI member institutions (Pauline & Pauline, 2008), but continue to show evidence that a minority of universities employ SPPs within athletics or counseling centers (Hayden et al, 2013;Pauline & Pauline, 2008;Voight & Callaghan, 2001;Wrisberg et al, 2012).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The best way to achieve this collaborative approach between services, professionals, and community groups is to coordinate regular multidisciplinary team meetings to discuss and evaluate the progress of individual athletes. When coordinating these multidisciplinary teams, each campus must decide which professionals, services, and organizations should be included within this network of collaborative care, identify their framework for collaboration, and then determine how the university's infrastructure will synchronize efforts to serve student-athletes (Hayden, Kornspan, Bruback, Parent, & Rodgers, 2013;Zakrajsek, Steinfeldt, Bodey, Martin, & Zizzi, 2013).…”
Section: Campus Community Levelmentioning
confidence: 99%